Computer technology integration and teachers’ knowledge and self-efficacy: Barriers and promise - Azeema, Fathimath; Talib, Othman; Othman, Azraai (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
The purpose of the study is to examine teachers’ technology integration level and teachers’ technology knowledge level in teaching and learning In addition, to determine whether there is a relationship between teachers’ knowledge, self-efficacy and technology integration in teaching and learning in secondary schools of Maldives. Furthermore, to find out if there is a difference in technology integration for science and non-science subject teachers. Study is a correlation study that uses quantitative methods. Sample size of 128 secondary teachers was selected from capital city Male’. Cluster random sampling method was used to randomly select the secondary schools. Data was gathered using survey questioner and data was analyzed using descriptive and inferential statistical techniques. Results revealed that teachers often integrated technology in teaching and learning and teachers had intermediate knowledge regarding how to use technology. Teachers were proficient with basic technology knowledge, however they lack the advance knowledge needed for more complex tasks. A positive correlation was found between technology knowledge, self-efficacy and technology integration. A significant difference was found for technology integration between science subject teachers and non-science subject teachers. These findings could be helpful for school administrators, to encourage teachers to use new technologies in teaching and learning. Findings from this study could be used to conduct future research and to improve current education system.